Purification, Identification, and Characterization of an Endo-1,4-β-Xylanase from Wheat Malt - Peng, Zhaojun (Molecules, 2020)
In this study, an endo-1,4-β-xylanase was purified from wheat malt following the procedures of ammonium sulfate precipitation, cation-exchange chromatography, and two-step anion-exchange chromatography. The purified endo-1,4-β-xylanase had a specific activity of 3.94 u/mg, demonstrating a weight average molecular weight (Mw) of approximately 58,000 Da. After LC–MS/MS (Liquid chromatography-tandem mass spectrometry) identification, the purified enzyme had the highest matching degree with a GH10 (Glycoside Hydrolase 10) domain-containing protein from wheat, there were 23 match peptides with a score above the threshold and the prot-cover was 45.5%. The resulting purified enzyme was used to investigate its degradation ability on high viscosity wheat-derived water-extractable arabinoxylan (WEAX). Degradation experiments confirmed that the purified enzyme was a true endo-acting enzyme, which could degrade large WEAX into smaller WEAX. The average degree of polymerization (avDP) and the viscosity of WEAX decreased with the increasing reaction time. The enzyme could degrade a small amount of WEAX into arabinoxylan-oligosaccharides (AXOS) with a degree of polymerization of 2–6, but no monosaccharide was produced. The degradation occurred rapidly in the first 3.5 h and decreased with the further prolongation of reaction time.